Gambaran Kadar Kolesterol Total pada Pecandu Kopi Kecamatan Poasia Kota Kendari - Darmayani, Satya; Rosanty, Anita; Rahmayani, Dian (Health Information : Jurnal Penelitian, 2018)
One of the effects of coffee consumption that still questionable is the increase in total cholesterol levels. The content of cafestol in coffee beans could be expected to block the process of ?-oxidation of cholesterol that increases cholesterol levels in the blood. This study aimed to describe the normal total cholesterol levels and high total cholesterol levels in coffee addicts in the working area of Puskesmas Poasia, Subdistrict of Poasia. The research sample amounted to 38 people taken by purposive sampling. The results showed that the total cholesterol levels test in coffee addicts obtained as many as 14 people (36.84%) with normal total cholesterol levels and as many as 24 people (63.16%) had a high total cholesterol level, but from 24 people of the coffee addicts, there are 4 of them in young age and allowed the possibility of an increase in cholesterol levels become faster due to genetic, lifestyle and unhealthy diet. It concluded that of the 38 people of coffee addicts who tested the cholesterol levels, the number of coffee addicts with high total cholesterol levels more than coffee addicts with normal total cholesterol levels. Therefore, it suggested people reduce consumption of coffee, especially those for coffee addicts.